PRINSIP KESANTUNAN DALAM NOVEL RINDU KARYA TERE LIYE - Syariah, Syariah; Martono, Martono; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThe research about principle of politeness in a novel Rindu by Tere Liye is based on curiosity toward implementation of principle of politeness in a novel Rindu that has various background of ethnic and culture, social status, and gap of different ages. This research specialize to clarify six maxim of principle oof politeness in a novel Rindu by Tere Liye and to implemented the result in a school. The method of research applied descriptive research method in qualitative form. The data collected from expression said by characters in novel Rindu, either in sentences, phrase, or words said to partners or listeners. The data resource taken from a novel Rindu by Tere Liye. The analysis data technique that is used in this research is descriptive qualitative. Based on the analysis toward 169 data that researcher found in the novel Rindu by Tere Liye, consist of 29 expressions that present wisdom maxim, 37 expression of generosity maxim, 43 expressions as appreciation maxim, 14 expressions present wisdom of simplicity, 21 expressions about consent maxim and 18 expression for inference maxim. The research result can be implemented in learning of Bahasa in the class XII second semester with KD 3.5 to evaluate the texts in the novel based on the rules either oral or written. Key words: principle of politenss, maxim, novel Rindu